L’approche territoriale de l’intégration des SER dans les zones montagneuses. L’aménagement participatif à l’aide des représentations 3D : exemples d’application en Méditerranée orientale - Dimitrios Goussios; Ioannis Faraslis; Prodromos Mardakis (Revue de Géographie Alpine)
Harmonising energy transition with the process of territorial development represents a substantial challenge for local mountain communities. This effort to harmonize RES (renewable energy sources) integration must escape the restrictive geometric and “point” approach to regulating the relationship between RES and landscape, and incorporate places included in the process of territorialisation by local communities. By incorporating functions and territorial resources, this transition modifies the nature and dimensions of the interfaces between the impacts of RES (landscape, land) and places of interest. As a result, it can determine the fields of a new regulatory framework for planning (location-resource-function-relationship). It can also contribute to the expansion of the definition of RES carrying capacity, which is constrained by the institutional framework. This whole process of harmonising RES integration reveals the need for local community participation in planning: as managers of territorial resources and as a source for a “territorial” information system through geo-visualisation. The whole methodological process incorporates territorial information in the planning of complex spatial issues, such as the integration of RES in territorial mountain areas. This process ultimately renews interactive participatory planning in a field where centrally—designed RES policy meets the bottom-up dynamics of territorialisation.